PENGARUH PROMOSI PENJUALAN, CITRA MEREK, DAN NILAI YANG DIRASAKAN DENGAN VARIABEL INTERVENING WOM TERHADAP KEPUTUSAN PENGGUNAAN KARTU KREDIT - Ayu Pratiwi Eka Risti; Muhammad Nadjib Usman (STIE Perbanas Surabaya, 2016)
This research explains one of the factors that sales promotion, brand image and perceived values which felt with intervening variable word of mouth against the customers decision using of credit card bank CIMB Niaga. Questioner distributed to 120 respondents in Surabaya and surrounding areas. Data analyzed using the Structural Equation Model (SEM) used to analyze the relationship between the variables examined. The result shows that variable sales promotion, brand image have a positive impact to the decision of the customers , while brand image also have a positive impact against wom in influencing the decision of the customers, but WOM has negative impact against decision to used credit card.